Short stature for age in children of 5 to 16 years: The first research from the Northern Himalayan region of India - Karishma Sharma; Vishakha Sharma; Vinod Kumar; Nowneet Bhat; Swathi Chacham; Vyas K Rathaur; Prashant K Verma (Wolters Kluwer Medknow Publications, 2023)
Introduction: Anthropometric parameters play vital role in monitoring growth in pediatrics. Many etiological factors lead to short stature. So, before assessing the etiological factors short stature needs to be addressed. This study aimed to screen short stature for age in school-going children aged 5 to 16 years in Uttarakhand. Material and Methods: In this cross-sectional observational study, the height (through stadiometer) and weight (through weight machine) of 4189 students of government and private school in Rishikesh (Uttarakhand) aged 5-16 years were measured after the verbal assent of the students and individual's height is in the 3rd percentile for the mean height of a given age, sex, and population group and was considered short stature. The data collection was performed from October 2019 to July 2021. The data were categorized according to different age groups to 5-8 years, 9-12 years, and 13-16 years. The data were recorded in Microsoft (MS) Excel spreadsheet program. Statistical Package for the Social Sciences (SPSS) v23 (IBM Corp.) was used for data analysis. Descriptive statistics were elaborated in the form of means or standard deviations and medians or Interquartile range IQRs for continuous variables and frequencies and percentages for categorical variables. The Chi-square test was used for group comparisons for categorical data. Results: 7.1% of children were short stature (height 143.16 ± 15.09 cm) in the Himalayan belt, and males were more prone to short stature at age of 9-12 years. Conclusion: In the growing phase of children, the etiology of short stature has to be rectified, so the children can achieve such proper growth. Parents and physicians have to assess and monitor the growth of children timely. This study can be a stepping stone for further epidemiological studies.